Kemampuan Pemecahan Masalah Siswa Kelas V pada Materi Geometri Ditinjau dari Gaya Kognitif - Vivi Dwi Ramadhani; Goenawan Roebyanto; Siti Umayaroh (Universitas Negeri Malang, 2019)
Abstract: Learning mathematics can develop students' thinking patterns in solving problems. The purpose of this study is to describe the ability to solve geometry problems based on independent and field dependent cognitive styles in fifth grade students of SD Karangbesuki 2 Malang. The research subjects consisted of 2 students with independent field cognitive styles and 2 students with field dependent cognitive styles. Based on the results of the study, students who have independent field cognitive style in this study are able to solve geometry problems based on Polya's steps, namely (1) able to find aspects that are known and asked, (2) able to draw up problem solving strategy relevant to what was asked, (3) able to solve the problem correctly, and (4) able to draw conclusions from the answers. Whereas students who have a field dependent cognitive style experience difficulties, namely (1) not including complete information, (2) being less able to prepare a completion plan, (3) the results of the answers are less precise, (4) not doing a look back step. Abstrak: Pembelajaran matematika dapat mengembangkan pola berpikir siswa dalam memecahkan masalah. Tujuan penelitian ini untuk mendeskripsikan kemampuan pemecahan masalah geometri berdasarkan gaya kognitif field independent dan field dependent pada siswa kelas V SDN Karangbesuki 2 Kota Malang. Subjek penelitian terdiri dari 2 siswa dengan gaya kognitif field independent dan 2 siswa dengan gaya kognitif field dependent. Berdasarkan hasil penelitian diketahui bahwa siswa yang memiliki gaya kognitif field independent pada penelitian ini mampu melakukan pemecahan masalah geometri berdasarkan langkah-langkah Polya, yaitu (1) mampu menemukan aspek yang diketahui dan ditanyakan, (2) mampu menyusun rencana yang relevan dengan yang ditanyakan, (3) mampu menyelesaiakan masalah dengan benar, dan (4) mampu membuat kesimpulan dari jawabannya. Sedangkan pada siswa yang memiliki gaya kognitif field dependent mengalami kesulitan, yaitu (1) belum mencantumkan informasi yang lengkap, (2) kurang mampu dalam menyusun rencana penyelesaian, (3) hasil akhir jawaban kurang tepat, (4) tidak melakukan pemeriksaan kembali.